The overexpression of an Amaranthus hypochondriacus NF-YC gene modifies growth and confers water deficit stress resistance in Arabidopsis - Palmeros-Suárez, Paola A (Plant science : an international journal of experimental plant biology, 2015)
Copyright © 2015 Elsevier Ireland Ltd. All rights reserved.